Characterization of a Nanovaccine Platform Based on an α1,2- Mannobiose Derivative Shows Species-non-specific Targeting to Human, Bovine, Mouse, and Teleost Fish Dendritic Cells - Pappalardo, Juan Sebastián (2021)
Dendritic cells serve as the main immune cells that trigger the immune response. We developed a simple and cost-effective nanovaccine platform based on the α1′,2-mannobiose derivative for dendritic cell targeting. In previous work, we have formulated the α1,2-mannobiose-based nanovaccine platform with plasmid DNA and tested it in cattle against BoHV-1 infection. There, we have shown that the dendritic cell targeting using this nanovaccine platform in vivo can boost the immunogenicity, resulting in a longlasting immunity. In this work, we aim to characterize the α1′,2-mannobiose derivative, which is key in the nanovaccine platform. This DC-targeting strategy takes advantage of the specific receptor known as DC-SIGN and exploits its capacity to bind α1,2-mannobiose that is present at terminal ends of oligosaccharides in certain viruses, bacteria, and other pathogens. The oxidative conjugation of α1′,2-mannobiose to NH2-PEG2kDa-DSPE allowed us to preserve the chemical structure of the non-reducing mannose of the disaccharide and the OH groups and the stereochemistry of all carbons of the reducing mannose involved in the binding to DC-SIGN. Here, we show specific targeting to DC-SIGN of decorated micelles incubated with the Raji/DC-SIGN cell line and uptake of targeted liposomes that took place in human, bovine, mouse, and teleost fish DCs in vitro, by flow cytometry. Specific targeting was found in all cultures, demonstrating a species-non-specific avidity for this ligand, which opens up the possibility of using this nanoplatform to develop new vaccines for various species, including humans.